HUBUNGAN SIKAP SISWA TERHADAP GURU DENGAN HASIL BELAJAR SISWA KELAS IV SDIT IMAM ASY-SYAFI’I KECAMATAN TAMPAN PEKANBARU - Fathiyah, Fathiyah; Syahrilpuddin, Syahrilpuddin; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Social Relationship Between Student Attitudes Teacher With Student Results Class IV-Imam Asy-Syafi'i SDIT Tampan District of Pekanbaru. This study aims to determine the relationship between Student Attitudes Teacher With Student Results Class IV-Imam Asy-Syafi’i SDIT Tampan District of Pekanbaru. The method used was a correlational techniques. The study population and the sample size is 31 by using saturated samples. Form of questionnaire data collection instruments. Attitude instrument validity Student Teacher tested using Pearson Product Moment Correlation formula. Student Teacher Attitudes reliability calculated using Spearman Brown formula. Based on the survey results revealed, for Student Teacher Attitudes categorized moderate(43%) were categorized and Learning Outcomes(52.63%). Tests conducted with test data normality Liliefors using α = 0.05 level. The results of the data analysis showed that There is a positive relationship between Teacher Student Attitudes(X) to the Learning Outcomes(Y) Primary School Isam al-Imam Asy-Syafi’i Tampan District of Pekanbaru with correlation coefficients at level rxy = 0.4069 α = 0.05. Student attitudes Teacher 16,56% contributed to the Learning Results. This means that the results can be improved with Attitude Learning Student Teacher.The results of this study are expected to be useful for the improvement of Student Attitudes Teacher With Student Results Class IV-Imam Asy-Syafi’i SDIT Tampan District of Pekanbaru. Conclusions The results of this study indicate that learning can be enhanced through the Student Teacher Attitudes.Keywords: Teacher Student Attitudes, Learning Outcomes.